Creative project work is the most effective learning tool for form 2 history lesson - Gurumoorthy Poobalan; Christina Micheal; Roslee Talip; Sukuneswari Kaliappan; Cheok, Jia Wei; Nur Ain Najwa Mohd Khairul Anuar (FPP, 2022)
Since early 2020, covid-19 transmission has caused the replacement of face-to-face classes with virtual classes. Even nowadays though face-to-face learning has begun to be fully implemented, the potential and abilities of students cannot be fully developed. However, knowing a subject for an hour in the classroom does not ensure the entire development of kids' talents and potential in terms of student's aspirations as design by Ministry of Education Malaysia. The short duration of the class and the limited involvement of students as a result of the big class size led to a lack of student engagement and the inability to improve problem-solving-oriented student results in the real world. Therefore, teaching and learning began to integrate creative project work. The application of creative project work in form 2 History lessons as an effective teaching and learning tool in the twenty-first century is the focus of this paper. The use of creative project work in teaching and learning can improve students' mastery of the subjects studied, increase learning motivation, improve collaboration, improve students' resource management skills, provide students with project management experience, provide learning experiences that are parallel to the real world, and provide a fun teaching process. Students will also be encouraged to build and practice communication skills as a result of this. The development of creative project work is comprised of multiple phases, including planning (curriculum content and objective),implementation, presentation, assessment and evaluation, and appreciation. As a result, application of creative project work into teaching and learning process increases students' academic achievement while also preparing them to confront future difficulties posed by social, economic, and global crises.